Multi-dimensional transitional dynamics: A simple numerical procedure - Timo Trimborn; Karl-Josef Koch; Thomas M. Steger (ETH Zurich, CER-ETH - Center of Economic Research, 2004)
We propose the relaxation algorithm as a simple and powerful method for simulating the transition process in growth models. This method has a number of important advantages: (1) It can easily deal with a wide range of dynamic systems including multi-dimensional systems with stable eigenvalues that di.er drastically in magnitude. (2) The application of the procedure is fairly user friendly. The only input required consists of the dynamic system. (3) The variant of the relaxation algorithm we propose exploits in a natural manner the in.nite time horizon, which usually underlies optimal control problems in economics. Overall, it seems that the relaxation procedure can easily cope with a large number of problems which arise frequently in the context of macroeconomic dynamic models. As an illustrative application, we simulate the transition process of the well-known Jones (1995) model.
Keywords: C61; C63; O40; 330; saddlepoint problems; transitional dynamics; economic growth; multidimensional stable manifolds; Wachstumstheorie; Schätztheorie; Nichtlineare Optimierung; Theorie